Association between Serum Levels of Vitamin D, Vitamin B12 and Folate with Oxidative Biomarkers in Diabetic Type 2 Patients in People in Erbil City: A Case-Control Study - Ismael Ibrahim , Gulzar; Jameel Majeed, Hemn; Abdullah Yousif , Pshtiwan; Muhsin Abdulkareem, Saman (Diyala Journal of Medicine, 2020)
Background: Diabetes mellitus is the largest endocrine disorder in the world that refers to chronic hyperglycemia caused by impairment in both insulin secretion and action. Folate, vitamin B12, and vitamin D deficiency are related to the prevalence of type 2 diabetes mellitus. Objective: This study has been carried out to investigate the role of folate, vitamins B12, and D status during the progression of diabetic type 2 patients compared to non-diabetic control subjects. Patients and Methods: We measured the plasma levels of folate, vitamins B12, and D, along with blood glucose, HbA1c, and oxidative biomarkers in 50 diabetic type 2 patients and 50 healthy subjects used as a control group. Results: The findings revealed that the serum level of malondialdehyde (MDA) significantly increased in diabetic patients compared to healthy subjects, and the serum level of nitric oxide (NO) in T2D patients lower than in control. The concentration of vitamin D, B12, and folate in T2D patients significantly lower than non-T2D control. The results also showed a significant relationship between serum vitamin D, MDA, and NO with HbA1c, while there was an insignificant correlation between vitamin B12 and folate with HbA1c. Conclusion: The oxidative biomarkers and vitamins D, B12, and folate level can play an important role in the development and progression of T2D.